Cover Picture: Stability of Odd‐ Versus Even‐Electron Gas‐Phase (Quasi)Molecular Ions Derived from Pyridine‐Substituted N‐Heterotriangulenes (ChemPlusChem 2/2017). Issue 2 (20th December 2016) - Hitzenberger, Jakob F.; Dral, Pavlo O.; Meinhardt, Ute; Clark, Timothy; Thiel, Walter; Kivala, Milan; Drewello, Thomas
Abstract : The cover picture shows the symbiosis of quantum chemical theory and gas‐phase collision experiment by investigating the influence of the electronic state on stability of the radical cation ([ M ] + . ) and protonated triangulene ([ M +H] + ). The dissociation of the radical cation requires less energy due to the formation of an energetically favored extended aromatic π‐system. Details are given in the Full Paper by T. Drewello, M. Kivala et al. onpage 204 in Issue 2, 2017 (DOI:10.1002/cplu.201600416 ).